Zebrafish: A Model for Understanding Diabetic Complications - Jörgens, K.; Hillebrands, J.-L.; Hammes, H.-P.; Kroll, J. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Diabetes mellitus causes several vascular complications in patients, such as macrovascular problems including myocardial infarction, peripheral artery diseases and stroke and microvascular problems including nephropathy and retinopathy. Likewise, diabetes mellitus is associated with other complications such as neuropathy and delayed wound healing. The zebrafish has been used for decades as a model organism for studies in developmental biology. In fact several common and important developmental mechanisms have been identified in zebrafish which are similar in mammals. The zebrafish has short generation intervals and zebrafish embryos are transparent and therefore provide unique imaging opportunities. In combination with genetic manipulations, including gene silencing protocols by using morpholinos, mutant or transgenic fish lines, the zebrafish has become one of the most important models in developmental biology. Over and above, zebrafish is also an established model organism for several pathophysiological conditions which are related to human diseases. For instance, zebrafish is used as an inflammation and regeneration model because of its ability to partially compensate for organ loss (e. g., heart and fins). It is also used for drug screening, in tumor biology, for systems biology, congenital and hereditary disease, and in infection 1.
Keywords: cardiovascular incidences; cardiovascular risk management; zebrafish